Antimicrobial resistance in human populations: challenges and opportunities. (2017) - Allcock, S.; Young, E. H.; Holmes, M.; Gurdasani, D.; Dougan, G.; Sandhu, M. S.; Solomon, L.; Török, M. E.
Abstract: Antimicrobial resistance (AMR) is a global public health threat. Emergence of AMR occurs naturally, but can also be selected for by antimicrobial exposure in clinical and veterinary medicine. Despite growing worldwide attention to AMR, there are substantial limitations in our understanding of the burden, distribution and determinants of AMR at the population level. We highlight the importance of population-based approaches to assess the association between antimicrobial use and AMR in humans and animals. Such approaches are needed to improve our understanding of the development and spread of AMR in order to inform strategies for the prevention, detection and management of AMR, and to support the sustainable use of antimicrobials in healthcare.